Public sector players in non-life insurance: will they survive? - Singh, Raghbir; Garg, Arunesh (2006)
The Indian insurance market was thrown open to private players in the year 1999. The liberalized Indian insurance market has seen the entry of a number of private non-life insurance players. Private players have been able to capture a significant market share in the non-life insurance market. It is firmly believed that ultimately, most of the non-life insurance market will be taken over by private sector players, and public sector players will have to face a tough time. The leader in non-life insurance in the private sector is ICICI Lombard, which in 2004-05, had underwritten a premium of Rs.873.87 cr. None of the private sector players, except ICICI Lombard and Bajaj Allianz, has been able to cross a figure of Rs.500 cr. Prior to liberalization, the contribution of public sector players in the growth of non-life insurance sector was very less. But, after the liberalization of insurance sector, the growth rate per annum has increased gradually. Hence, the declining market share of public sector players should not be taken as an erosion of their business levels. Public sector companies have to leverage upon their strengths to give a tough fight to the private sector players. - Reproduced.
Keywords: Public sector; Insurance